CHRONIC EPSTEIN-BARR VIRUS-ASSOTIATED HEPATITIS - Bodnar, V. (World of Medicine and Biology, 2014)
The patients with hepatitis need a complex clinic and laboratory examination for diagnostic of chronic replication Epstein-Barr virus infection. Chronic Epstein-Barr virus-assotiated hepatitis have a polymorphic clinical current with combination signs of dysfunction of liver and typical manifestation of Epstein-Barr-virus infection: expressive asthenic, abdominal pain, dyspeptic syndromes, fever, generalized lymphodenopathy, tonsillopharingitis, hepato-, splenomegaly, cytolysis cholestasis and dysproteinemia.
Keywords: hepatitis; Epstein-Barr-virus infection; clinical current; laboratory signs